2017
DOI: 10.1080/14763141.2017.1371215
|View full text |Cite
|
Sign up to set email alerts
|

The effects of limb dominance and a short term, high intensity exercise protocol on both landings of the vertical drop jump: implications for the vertical drop jump as a screening tool

Abstract: The effectiveness of vertical drop jumps (VDJs) to screen for non-contact ACL injuries is unclear. This may be contributed to by discrete point analysis, which does not evaluate patterns of movement. Also, limited research exists on the second landing of VDJs, potential lower limb performance asymmetries and the effect of fatigue. Statistical parametric mapping investigated the main effects of landing, limb dominance and a high intensity, intermittent exercise protocol (HIIP) on VDJ biomechanics. Twenty-two ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…Only ankle angle (θ cont and θ min ) of HS was affected by fatigue by comparing the shoe performance between fatigue intervention. The knee and hip angles (θ cont and θ min ) were similar to the findings of Whyte, et al [46]. They found no significant changes in joint angles at the initial landing phase.…”
Section: Joint Kinematicssupporting
confidence: 87%
“…Only ankle angle (θ cont and θ min ) of HS was affected by fatigue by comparing the shoe performance between fatigue intervention. The knee and hip angles (θ cont and θ min ) were similar to the findings of Whyte, et al [46]. They found no significant changes in joint angles at the initial landing phase.…”
Section: Joint Kinematicssupporting
confidence: 87%
“…After blood samples were collected, participants performed a single leg squat (SLS) and single leg crossover dropdown (SCD) on their dominant leg and a drop vertical jump (DVJ). [4] The dominant leg was chosen for analysis because previous studies have reported athletes are at a greater risk for injury on their dominant leg [23]. For the SLS, participants were instructed to cross their arms over their chest, bend their non-dominant leg, squat down as low as they could without touching the ground, and ascend to a neutral stance.…”
Section: Methodsmentioning
confidence: 99%
“…Four studies included a ballet/dance population (Abergel et al, 2020;Liederbach et al, 2014;Smeets et al, 2020;Wild et al, 2017). Three studies examined university athletes (Whyte et al, 2018a(Whyte et al, , 2018b(Whyte et al, , 2018c, and one study evaluated athletes performing strength training programs (Rabello et al, 2021). Finally, nine studies investigated recreational athletes (Gafner et al, 2018;Hollman et al, 2012;Kim et al, 2015Kim et al, , 2021Lessi et al, 2018;Matsunaga et al, 2021;Patrek et al, 2011;Smeets et al, 2019;Weinhandl et al, 2011).…”
Section: Study Characteristics 1 Participants' Characteristicsmentioning
confidence: 99%